Perioperative management of patients with rheumatic disorders: problems and solutions - A. A. Klimenko; A. A. Kondrashov (Klinicist)
Currently management of patients with rheumatic disorders (RD) involves not only application of all of the known spectrum of mediations in accordance with current guidelines and algorithms but also timely use of high-tech medical care, for example, endoprosthesis of the large joints, spinal surgery, dental care, endovascular surgery, aimed at decreasing the level of disability and improving patients’ quality of life. The article considers modern approaches to management of patients with RD in the perioperative period, special emphasis is given to administration of background anti-inflammatory and genetically engineered biological medications, as well as prevention of thrombosis of the deep veins and thromboembolic complications. In the postoperative period, use of pharmacological control of development of “painful endoprosthesis” is vital as it is the main cause of unsatisfaction with the outcome of orthopedic aid. An effective method for controlling pain syndrome in patients with RD is use of non-steroidal anti-inflammatory drugs (NSAIDs). Selection of a specific NSAID should be based on the knowledge of gastrointestinal and cardiovascular side effects, as well as evidence of effectiveness in the perioperative period. In the group of patients with RD, namely with ankylosing spondylitis and psoriatic arthritis, prevention of heterotopic ossification after orthopedic manipulations, endoprosthesis is very important. Considering high comorbidity in RD, it is necessary to determine perioperative risk taking into account patient’s condition and operative urgency: to evaluate clinical features of the main and concomitant disorder (ischemic heart disease, cerebrovascular pathology, diabetes mellitus, chronic kidney disease), type of the surgery, results of electrocardiogram at rest, lab tests, and other noninvasive procedures. Correct planning of management of the perioperative period in patients with RD, adequate pain relief prior to surgery and after it, early activization are the main elements of rehabilitation of patients with pathologies of the locomotor apparatus.